Peran Moral Reasoning dan Skeptisisme Profesional Memoderasi Role Stress Terhadap Perilaku Disfungsional Internal Auditor - Maha Dewi, Christina Ayu; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
Dysfunctional behavior of the auditor should be avoided to produce quality audit findings based on the fairness of a financial statement. The purpose of this study is to analyze the role of moral reasoning and professional skepticism moderating role stress on dysfunctional behavior of auditors. This research was conducted in all branch offices of PT Bank BRI Bali-Nusra Area as many as 29 offices by making the auditor as many as 107 people as sample with saturated sample method in test through regression analysis moderation technique (MRA). Based on the results of the analysis, role stress variables have a role in increasing dysfunctional behavior of auditors. Moral reasoning has a role in increasing dysfunctional behavior of auditors. Professional skepticism has a role in increasing dysfunctional behavior of auditors. Moral reasoning and Professional skepticism can strengthen the influence of role stress in increasing dysfunctional behavior of auditors. Keywords : role stress, moral reasoning, professional skepticism, auditor dysfunctional behavior